Investigating transformational leadership’s contribution to innovative work behavior through organizational culture and knowledge sharing - Primananda, Helmi Yahya; Palupi, Majang (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
This study investigates the impact of transformational leadership on innovative work behavior, examining organizational culture and knowledge sharing as potential mediators. Employing a quantitative research design, survey data were collected from 145 employees across 17 unit offices at PDAM Tirta Sembada Sleman. Data were gathered using a six-point Likert scale and were analyzed using structural equation modeling–partial least squares (SEM-PLS) with SmartPLS software. The results indicated that transformational leadership does not directly influence innovative work behavior. While organizational culture exhibits a positive effect, this effect is not statistically significant, and organizational culture does not mediate the relationship between transformational leadership and innovative work behavior. Conversely, knowledge sharing demonstrates a positive and significant influence on innovative work behavior, effectively mediating the relationship between transformational leadership and innovative work behavior. These findings suggest that transformational leadership alone is insufficient to stimulate innovation without effective knowledge-sharing. This study contributes to both theory and practice by underscoring the critical role of knowledge sharing as a mechanism connecting transformational leadership to innovation within public sector organizations. Limitations include the focus on a single organization and a relatively small sample size. The findings further emphasize the need to systematically and strategically integrate knowledge sharing into leadership and innovation initiatives.